Peter Sloterdijk: la música de las esferas y el olvido del ser desde todos los altavoces - autor, Sin (Nómadas. Critical Journal of Social and Juridical Sciences, 2006)
This work sets out an analysis of the contemporary transformations of the music idea, as well as of sociological and therapeutic the crossing of speeches and disciplines that try to give account of the aesthetic reach, of those transformations, those that, as it is, nourish the philosophical debate. Finally, to the light of the thought of the German philosopher Peter Sloterdijk, will outline a reading of the world like polyphonic system of sounds and an analogy between the music and the human life.